Strengthening Community Economics Based on The Tradition of Ngejot in Semarapura Kangin Klungkung - Agrosamdhyo, R.; Kusjuniati (Proceedings of Annual Conference on Community Engagement, 2022)
While several other provinces have experienced improved economic growth, the province of Bali has not experienced the same thing. This is because the economic sector in Bali Province, which relies on tourism activities, has been paralyzed by the Covid 19 pandemic. One of the affected areas is Klungkung Regency. Assistance from related parties, including universities in strengthening the local economy is highly expected. In general, the purpose of this activity is to reduce the negative impact of economic pressures that have not improved in Klungkung Regency, especially in Semarapura Kangin Klungkung. Economic Strengthening uses the Ngejot tradition-based, namely in the form of delivering food to relatives and neighbors of different religions during major religious holidays, such as Galungan for Hindus or Eid al-Fitr for Muslims. Ngejot is a tradition that refers to the concept of friendship in Islam and the concept of Katwang Asih in the teachings of Balinese Traditions. The results of this service are expected to be able to create a harmonious and harmonious life between religions in their daily lives and be able to strengthen the economy of the Semarapura Kangin community affected by the Covid 19 Pandemic.